A small molecule promotes cartilage extracellular matrix generation and inhibits osteoarthritis development - Shi, Yuanyuan (Nat Commun, 2019)
Degradation of extracellular matrix (ECM) underlies loss of cartilage tissue in osteoarthritis, a common disease for which no effective disease-modifying therapy currently exists. Here we describe BNTA, a small molecule with ECM modulatory properties. BNTA promotes generation of ECM components in cultured chondrocytes isolated from individuals with osteoarthritis. In human osteoarthritic cartilage explants, BNTA treatment stimulates expression of ECM components while suppressing inflammatory mediators. Intra-articular injection of BNTA delays the disease progression in a trauma-induced rat model of osteoarthritis. Furthermore, we identify superoxide dismutase 3 (SOD3) as a mediator of BNTA activity. BNTA induces SOD3 expression and superoxide anion elimination in osteoarthritic chondrocyte culture, and ectopic SOD3 expression recapitulates the effect of BNTA on ECM biosynthesis. These observations identify SOD3 as a relevant drug target, and BNTA as a potential therapeutic agent in osteoarthritis.